2000
DOI: 10.1192/bjp.177.6.499
|View full text |Cite
|
Sign up to set email alerts
|

Recent life events, cortisol, dehydroepiandrosterone and the onset of major depression in high-risk adolescents

Abstract: A subgroup of adolescents may carry a physiological risk for major depression which may be either of genetic and/or earlier psychosocial origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
243
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(265 citation statements)
references
References 24 publications
(24 reference statements)
15
243
2
5
Order By: Relevance
“…However, there is preliminary evidence that susceptibility to the mood-lowering effects of ATD may be of prognostic significance in patients with recurrent depression (Ruhé et al 2007). In addition, it appears that elevated cortisol secretion may have a role in predicting depression in high-risk individuals (Goodyer et al 2000 ;Harris et al 2000). Neurobiological markers, such as elevated cortisol, could help to guide early intervention studies in young people before the onset of recurrent illness.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is preliminary evidence that susceptibility to the mood-lowering effects of ATD may be of prognostic significance in patients with recurrent depression (Ruhé et al 2007). In addition, it appears that elevated cortisol secretion may have a role in predicting depression in high-risk individuals (Goodyer et al 2000 ;Harris et al 2000). Neurobiological markers, such as elevated cortisol, could help to guide early intervention studies in young people before the onset of recurrent illness.…”
Section: Discussionmentioning
confidence: 99%
“…However, this occurred in the context of physical health and memory problems, and one study lacked a non-depressed comparison group (Fiocco et al, 2006). Psychosocial factors have been related to a dysregulated diurnal profile in adolescents ( [Goodyer et al, 2000], [Greaves-Lord et al, 2007] and [ Van den Bergh et al, 2008]). With the exception of one study, which reported greater CARs in male university students with higher depression scores (Pruessner et al, 2003b), there is limited research examining diurnal cortisol and affect in young adults.…”
Section: Depression Anxiety Social Support and Cortisolmentioning
confidence: 99%
“…Inconsistencies in findings may be a function of different methods of sampling hormone levels [18] or differences in the kinds of acute and chronic stressful events studied [19]. With morning samples, the relationship between stress hormones and affective states was positive [20,21,22], whereas daytime or evening samples showed a negative relationship to distress onset (anxious or depressed moods) and poor performance [17,23], at least for cortisol and norepinephrine. Distress may affect not only absolute hormone levels but also the diurnal profile of hormone release [18,19].…”
Section: Introductionmentioning
confidence: 99%